2011
DOI: 10.1271/bbb.100588
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Sequence Analysis of Two Distinct Halotolerant Extracellular Proteases fromBacillus subtilisFP-133

Abstract: We cloned the genes encoding the two distinct extracellular halotolerant proteases of Bacillus subtilis FP-133 Expro-I and Expro-II, which were classified as alkaline serine and neutral proteases respectively. Three-dimensional modeling suggested that acidic and polar amino acid residues located on the surface stabilize protein structure in the presence of relatively high NaCl concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…3B). AprE JK and SB4 showed sequences similar to AprE FP133, 3) which also showed a similar result for salt resistance. Some other amino acid residues, including N109, N243, E251, D197, N252, and 259D has been reported to be related to salt resistance.…”
Section: )mentioning
confidence: 57%
See 2 more Smart Citations
“…3B). AprE JK and SB4 showed sequences similar to AprE FP133, 3) which also showed a similar result for salt resistance. Some other amino acid residues, including N109, N243, E251, D197, N252, and 259D has been reported to be related to salt resistance.…”
Section: )mentioning
confidence: 57%
“…Some other amino acid residues, including N109, N243, E251, D197, N252, and 259D has been reported to be related to salt resistance. 3,14) We found that there was no difference between CN2 and 168 at these sites except for 259D, which was replaced by 259S in AprE CN2. It is not clear whether D 259S can cause low salt resistance to AprE, although our data indicate that CN2 had low resistance to NaCl.…”
Section: )mentioning
confidence: 64%
See 1 more Smart Citation
“…The species of Bacillus described as halophilic to date are as follows: B. hemicentroti ( Chen et al , 2011 ); B. humanensis ( Chen et al , 2011 ); B. xianensis ( Sanchez-Porro et al , 2003 ; Schlegel et al , 1970 ); B. alkaliphilic ( Zhang et al. , 2012 ); B. halochares ( Pappa et al , 2010 ); B. chungangensis ( Cho et al , 2010 ) and B. subtilis ( Takenaka et al , 2011 ). Thus, the possibility that a new species of halophilic Bacillus was isolated from a compost process is noteworthy.…”
Section: Resultsmentioning
confidence: 99%
“…Bacillus subtilis strain FP‐133 is a moderately halotolerant bacterium that was isolated from fermented fish paste and produces several halotolerant hydrolytic enzymes . Extracellular serine protease and metalloprotease from strain FP‐133 have been purified and characterized , and their genes have been cloned . Strain FP‐133 produces other extracellular hydrolytic enzymes, some of which are stable and retain activity under moderately high salt conditions, and are therefore expected to be useful industrial enzymes.…”
Section: Introductionmentioning
confidence: 99%